2017
DOI: 10.1007/s10072-017-2959-9
|View full text |Cite
|
Sign up to set email alerts
|

Rs4878104 contributes to Alzheimer’s disease risk and regulates DAPK1 gene expression

Abstract: In 2006, a candidate gene study reported death-associated protein kinase 1 (DAPK1) rs4878104 variant to be significantly associated with Alzheimer's disease (AD) risk. However, the following studies showed inconsistent association results. Here, we conducted an updated analysis to investigate the potential association between rs4878104 and AD using a total of 60,751 samples (20,161 AD cases and 40,590 controls). In the pooled population, the results based on the allele and genotype genetic models show that rs4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…All statistical tests for heterogeneity and meta-analysis were computed using R Package 1 . More detailed meta-analysis methods have been widely described in previous studies ( Liu et al, 2013b , 2017a , b , 2018 ; Hu et al, 2017a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…All statistical tests for heterogeneity and meta-analysis were computed using R Package 1 . More detailed meta-analysis methods have been widely described in previous studies ( Liu et al, 2013b , 2017a , b , 2018 ; Hu et al, 2017a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…During recent years, with the rapid advance of next-generation DNA sequencing, identify disease-related mutation from large data set and develop treatment become possible (Cheng et al, 2016a, 2018a,b). Genome-wide comparison studies (GWASs) have identified a significant amount of common genetic variants associated with complex traits and diseases (Welter et al, 2014; Hu et al, 2017a,b). Many previous studies have identified genes such as APOE (Mahoney-Sanchez et al, 2016; Liao et al, 2017) on chromosome 19.…”
Section: Introductionmentioning
confidence: 99%
“…A Chinese research team validated these two gene variations (rs4877365 and rs4878104) with LOAD patients from the northern Han Chinese population in 2011, and the C allele of rs4878104 but not rs4877365 was recognized as a protective genetic factor of LOAD (odds ratio (OR): 0.75, p = 0.002), which provides the first evidence that DAPK1 allele-specific variants can influence the risk of developing LOAD in the Chinese population [82]. Although a much larger sample-based analysis showed a different conclusion from the previous one in that the rs4878104 variant is not significantly related to AD risk, it is significantly associated with AD susceptibility in the subgroup analysis [81].…”
Section: Dapk1mentioning
confidence: 65%